Situación inicial de la atención integrada a las enfermedades prevalentes de la infancia, Ciudadela 3 de Noviembre, año 2011 - Velásquez Pesántez, Jéssica M. (2013)
The strategy of integrated management of childhood illness (IMCI) is an integrated set of curative, preventive and promotion that provide both health services and at home and in the community. The overall objective of this research was to generate information on the knowledge, attitudes and practices of integrated management of childhood illnesses, identifying issues, risks and needs to promote responses from social actors also helped establish socio-demographic characteristics of the families under five years and the development of an action plan to improve health practices involving different stakeholders (mothers or caregivers, leaders, health, church, education)